Understanding collaborative teacher growth from the lens of digital learning agility: a pathway to educational excellence - Abdullah, Kamilah; Md Khambari, Mas Nida; Wong, Su Luan; Zakaria, Noor Syamilah; Abd Rahim, Nur Aira; Moses, Priscilla; Mohd Rosli, Nur Dania (Asia-Pacific Society for Computers in Education, 2024)
This study explores collaborative teacher growth through the lens of Digital Learning Agility (DLA) and its impact on teaching practices and professional development. Using qualitative methods and thematic analysis, the research highlights how fostering collaboration among educators can enhance instructional approaches and student outcomes, ultimately creating a supportive and innovative educational environment.